Immune-Neuroendocrine Interactions and Autoimmune Diseases. Issue 2 (2006) - Jara, Luis J.; Navarro, Carmen; Medina, Gabriela; Vera-Lastra, Olga; Blanco, Francisco
Abstract : The relationship between immune-neuroendocrine system is firmly established. The messengers of this connection are hormones, neuropeptides, neurotransmitters and cytokines. The immune-neuroendocrine system have the capacity to synthesize and release these molecules, which, in turn, can stimulate or suppress the activity of immune or neuroendocrine cells by binding to receptors. In fact, hormones, neuropeptides and neurotransmitters participate in innate and adaptive immune response. Autoimmune rheumatic diseases (ARD) are characterized by aberrant production of pro-inflammatory cytokines, which are a potent activator of the HPA axis. In consequence, high levels of pro-inflammatory hormones such as estrogens and prolactin, and low levels of glucocorticoids, an anti-inflammatory hormone, have been described in the active phase of ARD. In addition, high levels of pro-inflammatory hormones and cytokines have also been frequently detected in organ involvement of patients with ARD, suggesting an abnormal local neuroendocrine immune interaction. There is evidence that hormonal changes may appear before the symptomatic phase of the disease. Therefore, it is possible that a pro-inflammatory hormone favors the rupture of tolerance, which is a key feature of autoimmune diseases. The interactions between the immune-neuroendocrine system have a major impact on our understanding of the pathogenic mechanisms, diagnosis and therapy of ARD.